2022
DOI: 10.1186/s12876-022-02182-4
|View full text |Cite
|
Sign up to set email alerts
|

Machine learning-based survival rate prediction of Korean hepatocellular carcinoma patients using multi-center data

Abstract: Aim To predict survival time of Korean hepatocellular carcinoma (HCC) patients using multi-center data as a foundation for the development of a predictive artificial intelligence model according to treatment methods based on machine learning. Methods Data of patients who underwent treatment for HCC from 2008 to 2015 was provided by Korean Liver Cancer Study Group and Korea Central Cancer Registry. A total of 10,742 patients with HCC were divided in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 24 publications
0
4
0
Order By: Relevance
“…To categorize liver lesions identified on CT, Yasaka et al designed a model to differentiate liver lesions on CT into five categories: HCC, other malignant tumors, indeterminate masses, hemangiomas, and cysts, with a median AUC of 0.92 [46] . Most recently, the LiSNet AI tool was developed for staging of HCC aggressiveness using CT images, where Sun et al showed results comparable to subspecialist analysis [21] . A human-AI partnered diagnosis was also attempted, combining experience-based binary diagnosis and LiSNet, resulting in the best predictive ability for certain parameters such as microvascular invasion (MVI) with AUC 0.705 [21] .…”
Section: Ct Mri Petmentioning
confidence: 99%
See 2 more Smart Citations
“…To categorize liver lesions identified on CT, Yasaka et al designed a model to differentiate liver lesions on CT into five categories: HCC, other malignant tumors, indeterminate masses, hemangiomas, and cysts, with a median AUC of 0.92 [46] . Most recently, the LiSNet AI tool was developed for staging of HCC aggressiveness using CT images, where Sun et al showed results comparable to subspecialist analysis [21] . A human-AI partnered diagnosis was also attempted, combining experience-based binary diagnosis and LiSNet, resulting in the best predictive ability for certain parameters such as microvascular invasion (MVI) with AUC 0.705 [21] .…”
Section: Ct Mri Petmentioning
confidence: 99%
“…Most recently, the LiSNet AI tool was developed for staging of HCC aggressiveness using CT images, where Sun et al showed results comparable to subspecialist analysis [21] . A human-AI partnered diagnosis was also attempted, combining experience-based binary diagnosis and LiSNet, resulting in the best predictive ability for certain parameters such as microvascular invasion (MVI) with AUC 0.705 [21] .…”
Section: Ct Mri Petmentioning
confidence: 99%
See 1 more Smart Citation
“…At present, survival rates for HCC are still poor. 18 , 19 Therefore, significant efforts in early diagnosis and better treatment are certainly needed.…”
Section: Introductionmentioning
confidence: 99%